Implementation of Madrasah Head Supervision in Improving Teacher Personality Competence - Imayani, Imayani; Herman, Herman; Ayuningtyas, Dian (Seutia Hukamaa Cendekia, 2025)
The implementation of supervision plays an important role in the world of education, especially related to improving and enhancing the personality competence of teachers. This study aims to determine the planning, implementation, evaluation and follow-up of madrasah head supervision in improving the personality competence of teachers of Madrasah Tsanawiyah (MTs) Negeri 4 West Aceh. This research uses a qualitative approach with research subjects as many as 5 informants. Data collection techniques use observation, interviews and documentation, while data analysis techniques use data collection, data reduction, data presentation and conclusion drawing or data verification flow. The results of this study indicate that: 1) the planning of madrasah head supervision in improving teachers' personality competence is carried out through meetings with the entire board of teachers, preparation of the supervision agenda (supervision schedule), division of tasks and socialization of supervision instruments related to fostering teacher personality. 2) the implementation of madrasah head supervision in improving teachers' personality competence is carried out by conducting classroom visits, conducting observations, guiding teachers' personalities, holding meetings, group discussions and holding trainings. 3) Evaluation and follow-up of supervision results in improving teachers' personality competence is carried out in the form of an assessment from the madrasah head to the teacher, assessment among fellow teachers and assessment from students